123k views
3 votes
What method would be best to use 53=4(x-3)^2-11

1 Answer

5 votes

Answer:

x = 7 , -1

Explanation:

SOLUTION :-


4(x-3)^2-11 = 53

  • Add 11 to both the sides.


=> 4(x-3)^2-11+11=53+11


=> 4(x-3)^2 = 64

  • Divide both the sides by 4.


=> (4(x-3)^2)/(4) = (64)/(4)


=> (x-3)^2 = 16

  • Root square both the sides.


=> √((x-3)^2) = √(16)


=> x-3 = +4 \; or -4

Here , x will have two values -

1)
x-3 = 4


=> x = 4 + 3 = 7

2)
x - 3 = -4


=> x = -4 + 3 = -1

VERIFICATION :-

When x = 7 ,


4(x-3)^2 - 11 = 4(7 - 3)^2 - 11


= 4 * 4^2 - 11


= 4 * 16 - 11


= 64 - 11


= 53

When x = -1 ,


4(x-3)^2 - 11 = 4(-1 - 3)^2 - 11


= 4 * (-4)^2 - 11


= 4 * 16 - 11


= 64 - 11


= 53

User Hylowaker
by
5.6k points